152. CLINICAL OUTCOME OF NIVOLUMAB COMBINATION THERAPY AS 1ST LINE TREATMENT FOR ESOPHAGEAL CANCER IN A JAPANESE HOSPITAL (CHECKMATE 648). (24th September 2022) - Makino, Tomoki; Tanaka, Koji; Yamashita, Kotaro; Eguchi, Hidetoshi; Doki, Yuchiro
Abstract: Currently, immuno-checkpoint inhibitor (ICI) has been widely used for unresectable advanced/recurrent esophageal squamous cell carcinoma (ESCC) as 2nd or later line treatment, however clinical evidence regarding efficacy or safety of the 1st line ICI treatment for ESCC remains limited. The global phase 3 CheckMate 648 (ONO-4538-50) demonstrated significant overall survival (OS) benefit of nivolumab + chemotherapy and nivolumab+ ipilimumab versus chemotherapy (5FU/CDDP) in previously untreated patients with advanced ESCC with an acceptable safety profile. A total 970 ESCC patients with unresectable advanced/recurrent disease were randomized globally and this post-hoc exploratory subgroup analysis presented here includes only the 34 patients randomized and treated at this hospital during Dec, 2017-Dec, 2019. Treatment efficacy and adverse events were assessed among the three groups; nivolumab (3 mg/kg every 2 weeks) + ipilimumab (1 mg/kg every 6 weeks) (Group A, n = 11), nivolumab (240 mg every 2 weeks) + 5FU/CDDP (5FU800 mg/m2 day1–5/CDDP80 mg/m2 day 1、every 4 weeks) (Group B, n = 13) and 5FU/CDDP (5FU800 mg/m2 day1–5/CDDP80 mg/m2 day 1、every 4 weeks) (Group C, n = 10). Patient characteristics of the group A/B/C were as follows; age = 69 (52–82)/70 (52–85)/70 (55–75), gender (male/female) = 11:0/10:3/9:1. Regarding survival analysis (median follow-up time; 19.5 months) of Jan 24th, 2022, median OS were not reached in the group A, 15 months (95%CI = 5–28) in the group B and 12 (95%CI = 2–25) months in the group C. The most common treatment-related adverse events (≥ grade3) were pruritus in 2 cases, rash in 2 (Group A), neutropenia in 5 cases, leukopenia in 3, and anorexia in 3 (Group B) and no cases (Group C). No treatment-related death was identified in any groups. The results from this Japanese single-center exploratory subgroup analysis are consistent with the global study results, and support nivolumab + ipilimumab and nivolumab + chemotherapy as promising first-line treatments for patients with unresectable advanced/recurrent ESCC. Also, establishment of useful biomarker in distinguishing use of nivolumab + chemotherapy and nivolumab+ ipilimumab would be urgent.